2007
DOI: 10.1080/10284150701250747
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of antioxidant vitamins and carotenoids are low in individuals with a history of attempted suicide

Abstract: A history of attempted suicide is associated with low levels of antioxidant vitamins and carotenoids. Clinical importance of low antioxidants in attempters and interventional opportunity warrant further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
3
24
0
2
Order By: Relevance
“…Although the evidence to date is preliminary, levels of antioxidants, vitamins, and carotenoids have also been found to be lower in patients with a history of suicide attempts (Li et al , 2007). Investigators have speculated that lowered antioxidant capacity may impair protection against ROS, thus damaging fatty acids (Edwards et al , 1998, Maes et al , 1999).…”
Section: Oxidative Stress Cholesterol and ω3 Fatty Acids In The Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the evidence to date is preliminary, levels of antioxidants, vitamins, and carotenoids have also been found to be lower in patients with a history of suicide attempts (Li et al , 2007). Investigators have speculated that lowered antioxidant capacity may impair protection against ROS, thus damaging fatty acids (Edwards et al , 1998, Maes et al , 1999).…”
Section: Oxidative Stress Cholesterol and ω3 Fatty Acids In The Patmentioning
confidence: 99%
“…Therefore, it is important to prevent depressive episodes due to vitamin/mineral deficiency, particularly for people under high levels of stress. The role of nutrients in the treatment of depression and suicidal behaviors has been extensively studied in the civilian population (Cocchi et al , 1980, Papakostas et al , 2005, Enya et al , 2004, Li and Zhang, 2007, Sowa-Kucma et al , 2008). Whether or not the nutrients may help as a strategy for the prevention or adjunctive treatment of depression or suicidal ideation in the military and civilian population remains underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Low serum levels of lycopene have also been associated with increased risk of psychiatric disorders (Li & Zhang 2007). A cross-sectional study using NHANES III data (n = 6680) observed an inverse association between serum levels of certain vitamins and carotenoids and whether subjects had attempted suicide (Li & Zhang 2007).…”
Section: Potential Health Benefits Of Lycopenementioning
confidence: 99%
“…A cross-sectional study using NHANES III data (n = 6680) observed an inverse association between serum levels of certain vitamins and carotenoids and whether subjects had attempted suicide (Li & Zhang 2007). Suicide attempters had lower levels of antioxidant vitamins and carotenoids in their serum than did nonattempters.…”
Section: Potential Health Benefits Of Lycopenementioning
confidence: 99%
“…116 Low serum levels of lycopene have also been associated with increased risk of psychiatric disorders. 117 A study with 17 adults with asthma treated with placebo, tomato extract (Lyc-o-Mato ® , 45 mg/day lycopene), and tomato juice (45 mg/day of lycopene) for 7 days showed reduced airway neutrophil influx and reduced sputum neutrophil elastase activity after the tomato extract and tomato juice treatment. During placebo treatment, plasma lycopene concentrations decreased, the percentage of neutrophils increased, and neutrophil elastase levels increased.…”
Section: Other Diseasesmentioning
confidence: 99%